Treatment of Catatonia With Ultrabrief Right Unilateral Electroconvulsive Therapy: A Case Series. Issue 3 (September 2015) - Kugler, Joseph L.; Hauptman, Aaron J.; Collier, Samuel J.; Walton, Amy E.; Murthy, Smitha; Funderburg, Linda G.; Garcia, Keith S.
Abstract : Abstract: Catatonia is a syndrome heterogeneous with regard to presentation and etiology. Electroconvulsive therapy (ECT) remains the first-line treatment for catatonia. Literature review reveals only a few published case reports on the use of right unilateral (RUL) ECT in catatonia, 1 case report on ultrabrief RUL ECT, and an absence of evidence on the relative effectiveness and tolerability of RUL versus bilateral ECT in treating catatonia. In contrast, there are multiple reports in the literature of robustly dosed bilateral ECT, often administered on consecutive days. Reasons for choosing this intervention over the better-tolerated RUL treatment include assumptions about its relative speed and/or breadth of efficacy. Here we present a case series of 13 catatonic patients treated in an academic center over the course of the last 3 years. Our experience suggests that ultrabrief RUL ECT can rapidly and effectively treat catatonia from diverse etiologies.